2016
DOI: 10.1016/j.yexmp.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of nitrogen mustard mediated skin injury by a novel indomethacin bifunctional prodrug

Abstract: Nitrogen mustard (NM) is a bifunctional alkylating agent that is highly reactive in the skin causing extensive tissue damage and blistering. In the present studies, a modified cutaneous murine patch model was developed to characterize NM-induced injury and to evaluate the efficacy of an indomethacin pro-drug in mitigating toxicity. NM (20 µmol) or vehicle control was applied onto 6 mm glass microfiber filters affixed to the shaved dorsal skin of CD-1 mice for 6 min. This resulted in absorption of approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 74 publications
2
26
0
Order By: Relevance
“…Of particular interest were our findings that throughout the pathogenic response to SM, extensive mast cell degranulation occurred (Joseph et al, 2011). Similar degranulation of mast cells in mouse skin has been reported following exposure to nitrogen mustard (Composto et al, 2016; Jain et al, 2014). Mast cells are known to release a variety of mediators that control hemostasis and inflammation during the early stages of tissue injury, and cellular proliferation and remodeling during later stages of wound repair suggesting that they are key to both processes (Joseph et al, 2016; Kennelly et al, 2011; Theoharides et al, 2012; Weller et al, 2006).…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Of particular interest were our findings that throughout the pathogenic response to SM, extensive mast cell degranulation occurred (Joseph et al, 2011). Similar degranulation of mast cells in mouse skin has been reported following exposure to nitrogen mustard (Composto et al, 2016; Jain et al, 2014). Mast cells are known to release a variety of mediators that control hemostasis and inflammation during the early stages of tissue injury, and cellular proliferation and remodeling during later stages of wound repair suggesting that they are key to both processes (Joseph et al, 2016; Kennelly et al, 2011; Theoharides et al, 2012; Weller et al, 2006).…”
Section: Introductionsupporting
confidence: 77%
“…1), was synthesized as previously reported (Young et al, 2010). Mice (male SKH1-Hr mice, 5–8 weeks of age, Charles River Laboratories, Wilmington, MA) were treated topically with an ointment containing 1% NDH4338 twice per day beginning 1 h after SM exposure (Composto et al, 2016). For analysis of mast cells, full thickness skin punch biopsies were collected 1, 3, 7, and 14 days post exposure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As many of these mediators play roles in mustard‐induced skin injury, inhibitors of mast cell degranulation have been proposed as potential countermeasures . In this regard, we have shown that an indomethacin prodrug that stabilizes mast cells suppresses mustard‐induced injury in mouse skin …”
Section: Upregulation Of Mediators Of Inflammation In the Skin Followmentioning
confidence: 99%